ORAL MANIFESTATIONS IN TYPE 2 DIABETES MELLITUS – LITERATURE REVIEW - Andreea Gabriela Wagner; Elena Preoteasa; Madalina Bicheru; Cristina Teodora Preoteasa (Romanian Journal of Oral Rehabilitation, 2023)
Introduction: Type two diabetes induces a series of changes in oral cavity, with a direct impact in oro-dental status and therapeutic interventions. The aim of this study was to identify the existing literature data regarding the oral changes induced by non-insulin-dependent diabetes mellitus and their therapeutic impact. Material and Method: The substructure of the review is based on the PRISMA 2020 statement. For data collection, the following databases were used: Pub Med, Cochrane Library, Science Direct, Medline, Google, following the keywords: “Oral manifestations in diabetes”, “Oral complications in diabetes”, “Diabetes and dental implants”, ” Oral lesions in diabetes”. Original works, published in international scientific journals in the last 13 years, in English, in the form of cross-sectional or prospective-analytical clinical studies, with more than 35 type 2 diabetic patients, were included. Results: Studies have shown that periodontal disease (80%), oral candidiasis, xerostomia (32%), halitosis (76%), carious processes with root localization (22%), periimplantitis (3%) and periapical lesions after devitalization in proportion of 50% bone resorption and poor bone quality are the most frequent oral manifestations in type 2 diabetic patients. Conclusions: Type 2 diabetes with an uncontrolled glycemic index favors the appearance of oral lesions, which require their detection and a correct management of the diabetic patient in conventional prosthetic treatment or on implants, with a periodic control to maintain oral health and preserve the quality of life.